2021
DOI: 10.4102/aveh.v80i1.619
|View full text |Cite
|
Sign up to set email alerts
|

Freight-related greenhouse gas emissions in the supply of spectacle and contact lenses

Abstract: Background: Climate change is a global challenge requiring mitigation from all economic sectors. Although the consequences of climate change are well documented, there are limited studies regarding greenhouse gas emissions generated by the optometric industry.Aim: This study explored the greenhouse gas emissions created from the freight-related distribution of spectacle and contact lenses to South Africa (SA) in 2019.Setting: Spectacle and contact lens distributors in SA and an optometric courier service in Kw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…It is incumbent upon healthcare practitioners to consider the complete lifecycle assessment of the products utilised in healthcare delivery and to advocate for incorporation of sustainable lens materials and processing techniques. 37 The ndings of this study warrant an urgent need to include sustainable waste management into health sciences curricula and continued professional education programmes for healthcare practitioners. By doing so, the healthcare sector can take signi cant steps towards reducing its environmental footprint.…”
Section: Discussionmentioning
confidence: 88%
“…It is incumbent upon healthcare practitioners to consider the complete lifecycle assessment of the products utilised in healthcare delivery and to advocate for incorporation of sustainable lens materials and processing techniques. 37 The ndings of this study warrant an urgent need to include sustainable waste management into health sciences curricula and continued professional education programmes for healthcare practitioners. By doing so, the healthcare sector can take signi cant steps towards reducing its environmental footprint.…”
Section: Discussionmentioning
confidence: 88%
“…Although this would avoid the labour costs involved with source separation, it may incur costs through the requirement of specific chemicals and processes. Failing which, it may be suggested that optical laboratories engrave a code on lenses to identify lens materials 51 to aid with lens sorting. With the advent of 3D lens printing, research would also need to be conducted on recycling capacity of the monomers used in the manufacture of such lenses.…”
Section: Implications Of and Measures To Promote Lens Recycling In So...mentioning
confidence: 99%
“…54,55 The benefits of print-on-demand technology include minimal supply chain challenges and associated emissions, no material wastage and reduced need for warehouse space or extensive stock-onhand. 51 Three-dimensional printing has also been extended to the manufacture of contact lenses using poly(hydroxylethyl acrylate) and methacrylate monomers. 56 Closed loop recycling is reported to be successful in the reuse of 3D print wastes; 57 however, this only resolves the challenges of post-industrial waste and not post-consumer waste.…”
Section: Industry Perspective On Lens Recyclingmentioning
confidence: 99%